2020
DOI: 10.1016/j.trecan.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cancer Models in Zebrafish

Abstract: Pediatric cancer is a leading cause of death idraw n children and adolescents. Improvements in pediatric cancer treatment that include the alleviation of longterm adverse effects require a deeper understanding of the genetic, epigenetic, and developmental factors driving these cancers. Here, we review how the unique attributes of the zebrafish model system in embryology, imaging, and scalability have been used to identify new mechanisms of tumor initiation, progression, and relapse and for drug discovery. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 81 publications
1
26
0
Order By: Relevance
“…Through exhaustive comparison of the human and zebrafish genome assemblies, it was found that 82% of disease-causing human genes have at least one zebrafish ortholog ( Howe et al, 2013 ). This level of conservation has led to the development of a wide array of cancer models in zebrafish ( Casey and Stewart, 2018 ; Hason and Bartůněk, 2019 ; Casey and Stewart, 2020 ; Elliot, 2020 ). Through the years of ongoing research, the pathological similarities of cancer and preservation of the immune components have also been well established between zebrafish and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Through exhaustive comparison of the human and zebrafish genome assemblies, it was found that 82% of disease-causing human genes have at least one zebrafish ortholog ( Howe et al, 2013 ). This level of conservation has led to the development of a wide array of cancer models in zebrafish ( Casey and Stewart, 2018 ; Hason and Bartůněk, 2019 ; Casey and Stewart, 2020 ; Elliot, 2020 ). Through the years of ongoing research, the pathological similarities of cancer and preservation of the immune components have also been well established between zebrafish and humans.…”
Section: Introductionmentioning
confidence: 99%
“…While zebra fish models might not be as translatable as mouse models due to their non-mammal nature, shorter generation times, higher scalability, lower costs, extracorporeal embryonic development, and skin transparency (allowing live cell imaging) render them a powerful and complementary modeling tool for pediatric tumors [ 150 ]. Good examples of such a genetically-engineered zebrafish models for pediatric sarcoma can be found in the study of Parant et al on MPNST [ 151 ] as well as the recent review of Casey et al on sarcoma zebrafish models for pediatric cancers [ 152 ]. For rhabdomyosarcoma an eRMS model expressing KRAS G12D in muscle satellites cells via Rag2 promoter by Langenau et al [ 153 , 154 ] as well as an aRMS model, systemically expressing the PAX3-FOXO1 fusion by Kendall et al [ 155 ] were developed to date.…”
Section: Established In Vivo Models Of Pediatric Sarcomamentioning
confidence: 99%
“…Noticeably, an impetus to move zebrafish models toward personalized and precision medicine has been generated and is currently moving with considerable speed (Fior et al, 2017 ; Casey and Stewart, 2020 ; Costa et al, 2020a ; Fazio et al, 2020 ). In regard to zPDX, both larval and adult models have demonstrated their remarkable potential to help guide clinical decisions; deciding which developmental stage to use, however, will likely depend on (1) the patient's timeframe, (2) the quantity of patient-derived material, (3) the number of therapeutic options planned to be tested, and (4) the tumor/TME aspects of interest.…”
Section: Toward Adult Zebrafish Cancer Models and Zebrafish Patient-dmentioning
confidence: 99%